PENGEMBANGAN MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN PASSING DALAM PERMAINAN SEPAK BOLA PADA SMP IT DARUL FIY AZKYA PEKANBARU BERBASIS MOBILE ANDROID - Dani Fajrul; Aref Vai; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The development of this Android-based audiovisual as an alternative to student learning in developing football passing skills in terms of learning styles and variation models applied. The aim of this research is a solution to help students learn through an Android application in the form of audiovisual. The subjects used in this research were students of SMP IT Darul Fiy Azkya Pekanbaru, 8 subjects in small groups and 30 subjects in large groups. This type of research is research and development to produce descriptive products. The results of this survey show that from the results of the assessment of materials experts, namely 95% and media experts, and based on the results of large group trials, namely 90%. The developed product is in the form of audiovisuals that focus on developing football passing. Based on the feasibility test, the 79% value is categorized as achievable and the test results are assigned a 95% value with achievable category.Key Words: Audiovisual, Android Mobile, Football Passing